2016
DOI: 10.1007/s00018-016-2324-9
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cells in Marfan syndrome aneurysm: the broken bricks in the aortic wall

Abstract: Marfan syndrome (MFS) is a connective tissue disorder with multiple organ manifestations. The genetic cause of this syndrome is the mutation of the FBN1 gene, encoding the extracellular matrix (ECM) protein fibrillin-1. This genetic alteration leads to the degeneration of microfibril structures and ECM integrity in the tunica media of the aorta. Indeed, thoracic aortic aneurysm and dissection represent the leading cause of death in MFS patients. To date, the most effective treatment option for this pathology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 100 publications
1
33
0
Order By: Relevance
“…In normal human body, contractile phenotype of VSMCs plays an important role in maintenance of the vascular structure and function of the blood vessel wall. When TAD occurred, the number and rate of synthetic VSMCs are reported to be obviously increased, resulting in decreased aortic elasticity and rupture of blood vessel wall [2123]. These studies indicated that phenotype switch of SMCs may become a crucial factor implicated into the occurrence of TAD.…”
Section: Discussionmentioning
confidence: 99%
“…In normal human body, contractile phenotype of VSMCs plays an important role in maintenance of the vascular structure and function of the blood vessel wall. When TAD occurred, the number and rate of synthetic VSMCs are reported to be obviously increased, resulting in decreased aortic elasticity and rupture of blood vessel wall [2123]. These studies indicated that phenotype switch of SMCs may become a crucial factor implicated into the occurrence of TAD.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β pathway’s multi-functional role results in many context- and tissue-dependent functions, which are difficult to unravel (Pardali et al, 2010). Most studies on diseases of the great arteries have aimed to understand the role of TGF-β in SMCs (Li et al, 2014; Yang et al, 2016; Zhang et al, 2016; Perrucci et al, 2017; Takeda et al, 2018), overlooking its function in the endothelium. In EC biology, Alk5 function has been mostly studied in vitro , where it has been shown to maintain EC quiescence (Goumans et al, 2002; Goumans et al, 2003; Lebrin et al, 2004; van Meeteren and ten Dijke, 2012; Maring et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CVDs include a series of diseases affecting blood vessels, such as coronary artery disease, aortic aneurysms, cerebrovascular disease, peripheral artery disease, pulmonary hypertension and renal artery stenosis, as well as diseases affecting the heart. Vascular smooth muscle cells (VSMCs) are one of the foremost cellular types of vascular walls that regulate arterial vascular tone and maintain structural stability for blood flow together with elastic fibers [2,3]. In response to environmental changes, modulation of VSMC survival and function plays a crucial role in the development of CVDs.…”
Section: Introductionmentioning
confidence: 99%